Experienced vs Inexperienced Disabled Swimmers: Training Load and Recovery in Preparation Period - Ashadi, Kunjung; Handayani, Oktia Woro Kasmini; Setijono, Hari; Rustiadi, Tri; Sugiharto; Soegiyanto (Physical Education Theory and Methodology, 2023)
The study purpose was to analyse the training load and recovery of experienced and inexperienced swimmers with disabilities. Materials and methods. The study subjects consisted of seven swimming athletes with disabilities at the provincial level who underwent training camps in preparation for the Indonesia Paralympics Games. The groups of athletes were divided based on their level of training and experience in national championships. For thirteen weeks, the athletes monitored their training load and recovery rate. Borg CR-10 was used to measure the internal training load, while the athlete’s recovery rate was measured using Total Quality Recovery (TQR). IBM SPSS Statistics version 22 was used to analyse normality and test differences between the two groups. The Mann-Whitney test was used to test the significance of the RPE Borg CR-10, while the unpaired T-test was used to test the significance of the TQR. Results. The Borg CR-10 mean for the experienced athlete group was 7.78±0.47, while it was 8.28±0.56 (p<0.05) for the inexperienced athlete group. The RPE mean for the experienced athlete group was 18.24±1.47, while it was 18.52±1.57 (p>0.05) for the inexperienced athlete group. Furthermore, the Borg RPE shows the training load of experienced athletes of 17.12±1.03, which is lower than the average RPE of inexperienced athletes of 18.21±1.24, and also the TQR average of experienced athletes was of 18.24±1.47, while it was of 18.52 ±1.55 (p<0.05) in case of inexperienced athletes. Conclusions. Experienced para-swimmers had a significantly different training load than inexperienced para-athletes. In addition, the training load of experienced para athletes was also significantly different compared to the recovery rates of experienced and inexperienced para swimmers.